2015
DOI: 10.1007/s00284-015-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Hydrolytic Enzymes Exhibit Antibiofilm Activity Against Escherichia coli at Sub-Lethal Concentrations

Abstract: The effects of two commercially available immobilized enzymes (namely the glycosidase pectinase and the protease subtilisin A) at sub-lethal concentrations were investigated in terms of their influence on biofilm genesis, on the composition of the biofilm matrix, and their antibiotic synergy against Escherichia coli biofilm, used as a model system of bacterial biofilms. The best antibiofilm performance of solid-supported hydrolases was obtained at the surface concentration of 0.022 and 0.095 U/cm(2) with a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Among others (e.g., subtilisin Carlsberg from Bacillus licheniformis , lipase from Burkholderia cepacia or pectinase from Aspergillus niger ), α-CT was preferred as, in a previous work by these authors, this enzyme showed the highest transesterification activity once immobilized with GA [24,30]. Notably, the same authors observed an increase in the catalytic activity of α-CT after treatment with GA [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others (e.g., subtilisin Carlsberg from Bacillus licheniformis , lipase from Burkholderia cepacia or pectinase from Aspergillus niger ), α-CT was preferred as, in a previous work by these authors, this enzyme showed the highest transesterification activity once immobilized with GA [24,30]. Notably, the same authors observed an increase in the catalytic activity of α-CT after treatment with GA [31].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the enzyme used free in solution as well as in coatings, chemical immobilization ensures the retention of the catalytic activity, which allows the enzyme to be used repeatedly and continuously, as well as confining the protease activity where biofilm formation occurs [30,38]. Indeed, the nature of the covalent binding guarantees the long life of the material since molecules are permanently attached and integrated into the polymer scaffold structure [40], preserving the surrounding environment from enzyme contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selection pressure decreases, limiting resistant-drug development, and potentially reinstating the efficacy of traditional antimicrobials [69]. Several natural and synthetic compounds, as well as matrix-targeting enzymes based on the previous biocide-free anti-biofilm mechanisms of action, have been coated or immobilized on polymeric surfaces, providing promising, eco-friendly, bio-inspired, anti-biofilm materials able to replace, or integrate with, presently dominating biocide-based approaches [69,70,71,72,73,74].…”
Section: Anti-biofilm Polymeric Surfacesmentioning
confidence: 99%
“…These enzymes were widely used in food industry, such as fruit softening, fruit juice lucidification, and coffee and tea fermentations. Pec immobilized on membranes can be used as antibiofilm coating in the treatment of waste water [47,48]. A previous study reported that a fungal strain Aspergillus clavatus MTCC1323 can degrade the biofilms of Pseudomonas aeruginosa (P. aeruginosa) and Bacillus subtilis (B. subtilis) by produced enzymes such as Pec, protease, and amylase [49].…”
Section: Introductionmentioning
confidence: 99%